Author Correction: The genome sequence of allopolyploid Brassica juncea and analysis of differential homoeolog gene expression influencing selection. (November 2018) - Yang, Jinghua; Liu, Dongyuan; Wang, Xiaowu; Ji, Changmian; Cheng, Feng; Liu, Baoning; Hu, Zhongyuan; Chen, Sheng; Pental, Deepak; Ju, Youhui; Yao, Pu; Li, Xuming; et al.
Following publication of this article, the authors have corrected 426 chimeric scaffolds in this genome (total scaffold number 10, 684). The genome assembly has now been improved as V1.5, and the updated genome assembly is available to be downloaded fromhttp://brassicadb.org/brad/datasets/pub/Genomes/Brassica_juncea/V1.5/ .